Optimalisasi Peran Kader Dan Masyarakat Untuk Penemuan Ibu Hamil Trimester 1 Untuk Mendapatkan K1 Murni Di Puskesmas Sungai Turak - Sari, Dewi Purnama; Meldawati, Meldawati; Noor Hasanah, Siti (Pusat Riset dan Inovasi Nasional, 2024)
Analyzing the situation in society, there are still pregnant women who do not have their pregnancies checked early at the Community Health Center or Posyandu. A more intensive role of cadres and the community is needed, to find and provide support and encouragement, so that pregnant women in the first trimester have their pregnancies checked by health workers/midwives. The proposed solution is to increase the role of cadres and the community in Sungai Turak village, to be able to find pregnant women in the first trimester early. This community service activity is in the form of educational material provided to cadres and the community, so that cadres and the community can jointly find/detect pregnant women. The output of the activity is in the form of outreach material provided to cadres and the community. Activities will be carried out in December 2023 - January 2024. After the leaflet materials have been completed, outreach activities are scheduled for cadres and the community, which will be held on January 18 2024 at the Community Health Center. During the counseling process, information was conveyed about the importance of pregnancy checks, the role of cadres, and steps to motivate pregnant women to have their pregnancies checked at a health service.